2016
DOI: 10.1007/s12288-016-0683-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Plasma Fibrinogen in Diagnosis and Prediction of Short Term Outcome in Neonatal Sepsis

Abstract: The study was carried out to determine the role of plasma fibrinogen in diagnosis of neonatal sepsis and to evaluate its role in predicting short term outcome. Sixty five neonates with clinical features suggestive of neonatal sepsis were included in this study. Seventy five neonates served as the control group. Plasma fibrinogen, prothrombin time, activated partial thromboplastin time and platelet counts were performed in all the neonates. Cut-off value of plasma fibrinogen for diagnosis of neonatal sepsis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
1
15
0
3
Order By: Relevance
“…Previous study reported that lower level of plasma fibrinogen was detected in neonates who died, and plasma fibrinogen was proved to be an effective tool in assessing development of outcome in neonates [7]. Moreover, a dramatic increase in mortality was reported in patients with fibrinogen below 200 mg/dL in adult patients with severe sepsis [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous study reported that lower level of plasma fibrinogen was detected in neonates who died, and plasma fibrinogen was proved to be an effective tool in assessing development of outcome in neonates [7]. Moreover, a dramatic increase in mortality was reported in patients with fibrinogen below 200 mg/dL in adult patients with severe sepsis [6].…”
Section: Discussionmentioning
confidence: 98%
“…Recent report demonstrated that a fibrinogen level of approximately <200 mg/dL is associated with sharply increased mortality in adult patients with severe sepsis [6]. Moreover, neonates with sepsis who died displayed a lower level of plasma fibrinogen than survivors [7]. Hypofibrinogenemia is distinctive for a high mortality rate in septic children [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is an acute-phase protein, and its primary function is to stop excessive bleeding by forming a fibrin-based blood clot to occlude blood vessels, after enzymatic conversion to fibrin (catalyzed by thrombin) in tissue and at the sites of vascular injuries. 16 Some studies showed that fibrinogen plays a key role in activating and mediating the inflammation process, 17 and is a useful predictive marker for a variety of inflammation-related pathologies such as appendicitis, 18 periodontitis, 19 malaria, 20 and sepsis. 21 In addition, Li et al 22 performed a multicenter retrospective study of 565 patients and demonstrated that plasma fibrinogen levels were significantly higher in patients with PJI than in patients with aseptic failure (median: 4.82 g/L vs 3.11 g/L, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Despite coagulation markers such as Platelet Count and Mean Platelet Volume ratio [22], D-Dimer [23] and plasma Fibrinogen [24] have been used in in ammation and infection diseases diagnosis [10,11], the role of these coagulation markers in PJI diagnosis is still unknow. Although the role of D-Dimer [12][13][14] plasma Fibrinogen [16], Platelet Count and Mean Platelet Volume ratio [15] were evaluated in PJI diagnosis, and D-dimer > 1170 ng/m [14], PC/MPV > 31.70 [15] and FIB > 4.01 µg/mL [16] were recommend as the optimum threshold value for the PJI diagnosis, no subsequent studies were published thereafter.…”
Section: Discussionmentioning
confidence: 99%